Experiences, Insights and Reflections in the Discourse of Criticism of Lithuanian Cinema In the 1980s - Mažuolytė, Aistė (Vilnius University Open Series, 2024)
The narrative of the Lithuanian cinema development attempts to present the Soviet period in a coherent way, focusing on the impact of the Soviet system. However, a broader range of reasons for the malaise of Lithuanian cinema can be found in the criticism of the Lithuanian film cultural field participants. The object of this study is the critical thoughts on the Lithuanian film industry, production, and culture in the 1980s, as captured in the press. Various representatives of the film world and other cultural spheres were involved in the reflection on the poor state of Lithuanian cinema. They gave a radical negative description of the cinema condition and offered different points of view about its reasons. Even though the incompleteness of the thoughts testifies the critical discourse’s dependence on the Soviet system, the argumentative criticism offers a more diverse approach to the Lithuanian cinema in the 1980s.